Manajemen Sumber Daya Manusia dalam Meningkatkan Pendidikan Tinggi Islam - Kartika, Ika; Nurfitriah, Nurfitriah; Wibowo, Esa Hari; Yunita, Rini Irma; Supriadi, Ujang (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to determine human resource management in improving Islamic higher education. The method used is qualitative methodology with an analytical approach. The data is obtained based on facts, field realities, and not designed by researchers through research. The research concludes that the process of Islamic education management can provide improvement in Islamic higher education with religious values as its foundation.